Galectins in Intestinal Inflammation: Galectin-1 Expression Delineates Response to Treatment in Celiac Disease Patients - Sundblad, Victoria; Quintar, Amado A.; Morosi, Luciano G.; Niveloni, Sonia I.; Cabanne, Ana; Smecuol, Edgardo; Mauriño, Eduardo; Mariño, Karina V.; Bai, Julio C.; Maldonado, Cristina A.; Rabinovich, Gabriel A. (Frontiers in Immunology, 2018)
Galectins, a family of animal lectins characterized by their affinity for N-acetyllactosamine-enriched glycoconjugates, modulate several immune cell processes shaping the course of innate and adaptive immune responses. Through interaction with a wide range of glycosylated receptors bearing complex branched N-glycans and core 2-O-glycans, these endogenous lectins trigger distinct signaling programs thereby controling immune cell activation, differentiation, recruitment and survival. Given the unique features of mucosal inflammation and the differential expression of galectins throughout the gastrointestinal tract, we discuss here key findings on the role of galectins in intestinal inflammation, particularly Crohn's disease (CD), ulcerative colitis (UC), and celiac disease (CeD) patients, as well as in murine models resembling these inflammatory conditions. In addition, we present new data highlighting the regulated expression of galectin-1 (Gal-1), a proto-type member of the galectin family, during intestinal inflammation in untreated and treated CeD patients. Our results unveil a substantial up-regulation of Gal-1 accompanying the anti-inflammatory and tolerogenic response associated with gluten-free diet (GFD) in CeD patients, suggesting a major role of this lectin in favoring resolution of inflammation and restoration of mucosal homeostasis. Thus, a coordinated network of galectins and their glycosylated ligands, exerting either anti-inflammatory or pro-inflammatory responses, may influence the interplay between intestinal epithelial cells and the highly specialized gut immune system in physiologic and pathologic settings.